The determinants of knowledge of cervical cancer, attitude towards screening and practice of cervical cancer prevention amongst antenatal attendees in Ibadan, Southwest Nigeria - Agboola, Adebayo M D (Ecancermedicalscience, 2021)
Cervical cancer (CC) is an extremely preventable and curable disease with early detection and treatment. Unfortunately, the practice of cervical cancer prevention (CCP) remains poor in resource constrained countries. This study aimed to identify determinants of knowledge of CC, attitude towards cervical cancer screening (CCS) and practice of CCP among antenatal attendees in a tertiary hospital in Southwest Nigeria as they are sexually active women. This was a cross-sectional survey of a cohort of 287 antenatal attendees using a self-administered structured questionnaire to assess their knowledge of CC, attitude towards screening and uptake of screening and human papillomaviruses (HPVs) vaccination as methods of practice of CCP. Data was analysed using the Statistical Package for Social Sciences version 20.0. Descriptive statistics were conducted for all relevant data. Categorical variables were explored using chi-square test and the independent variables with significant associations (p-value < 0.05) entered into logistic regression analysis. The mean age was 30.62 ± 4.5 years. Three-fifths (60.6%) of the women had good knowledge of CC while 47.4% had heard about CCS. Majority (75.6%) were willing to undergo CCS thereby exhibiting positive attitude towards screening. The practice of CCP was poor as only 27 (9.4%) had ever been screened for CC while 10 (3.5%) had received the HPV vaccine. Interestingly, none of the women who had received the HPV vaccine had been screened for CC. Those with tertiary education were more likely (OR = 2.140, 95% CI = 1.166–4.979) to exhibit positive attitude to CCS, while those with poor knowledge were about two times less likely to have a positive attitude (OR = 0.532, 95% CI = 0.291–0.972). Poor knowledge of CC was associated with lesser odds (OR = 0.061, 95% CI = 0.008–0.471) of practice of CCP. In Nigeria, the burden of CC can be reduced if women are educated and health care providers challenged to recommend CCS and HPV vaccination.